THE CORRELATION OF TEXT, CO-TEXT, AND CONTEXT IN THE SOLO POS DAYLY NEWSPAPER EDITION 2021 - Sri Budiyono; Erry Pranawa; Gunawan Budi Santoso (English Review: Journal of English Education, 2022)
This study aims to describe how are the results of the correlation analysis of text, co-text, and context in the Solo Pos Daily Newspaper, 2021 edition; whether the correlation of text, context, and context in the 2021 edition of the Solo Pos daily newspaper is cohesive and coherent. This study used descriptive qualitative method. The object of this research is the correlation of text, context, and context in the 2021 edition of the Solo Pos Daily Newspaper. This study used descriptive qualitative analysis The results of the study show that in general (almost all) of the discourses in the 2021 edition of the Solo Pos Daily Newspaper, the structure has paid attention to the relationship between sentences so that they can establish linkages and coherence between these sentences. Meanwhile, in terms of form, it can be called a complete discourse. There is only one data that happens to be the way to understand it must look at the sentence before and after it. In short, all sentence structures presented in the Solo Pos Daily newspaper are grammatical, in the sense that they are grammatically arranged. The order of the language and the pattern of the arrangement is correct, it is in accordance with the grammar so that it can be concluded that the grammar is correct.